Mickiewiczowski ideał wychowawczy Romana Pollaka - Dambek-Giallelis, Zofia; Niewiarowska, Dagmara; Skrobała, Łukasz (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The article presents a previously unpublished lecture on Adam Mickiewicz by professor Roman Pollak, O idei wychowawczej Mickiewicza (On Mickiewicz’s pedagogic idea), which was created and given for the first time during the German occupation in Warsaw and then repeated in the early post-war years. The commentary locates this text in the context of Pollak’s biography and scientific interests; it also outlines the connection between the ideas presented in it and the philosophy and ethics in Mickiewicz’s Wykłady o literaturze słowiańskiej (Lectures on Slavic literature).